1980
DOI: 10.1177/00220345800590101301
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin as a Mediator of Bone Resorption Induced by Experimental Tooth Movement in Rats

Abstract: Administration of indomethacin inhibited the appearance of osteoclasts and bone resorption induced by experimental tooth movement in rats. Effects were limited to groups injected within 12 h after treatment. Prostaglandin E1 or E2 solutions injected in gingiva lying near the upper first molar caused the appearance of osteoclasts and bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
13

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(97 citation statements)
references
References 20 publications
2
82
0
13
Order By: Relevance
“…Thus, comparisons are difficult. Nevertheless, the exceptional effect of aluminum to stimulate bone formation without increasing resorption remains uniquely different from that of both prostaglandin E2 and fluoride (both of which enhance resorption) (29,32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, comparisons are difficult. Nevertheless, the exceptional effect of aluminum to stimulate bone formation without increasing resorption remains uniquely different from that of both prostaglandin E2 and fluoride (both of which enhance resorption) (29,32).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study coincide with the results of a study carried out by Spangenberg et al, who reported that psychological stress resulted in 14% weight loss in the stress group rats compared to the control group rats in 4 weeks (32). In a study the weight of the rats in the stress group was less than that in the control group (33). Other researchers have reported that psychological stress gives rise to weight loss in rats (34).…”
Section: E290mentioning
confidence: 90%
“…In our experiment, we moved the maxillary first molar tooth in an anterior direction (opposite to the direction of physiologic distal drift), which induced a bone remodeling pattern opposite to that observed during physiologic drift. This change probably occurs as a result of changes in the stress/strain forces on the periodontium produced by the experimental forces on the adjacent teeth (Macapanpan et al, 1954;Waldo and Rothblatt, 1954;Zaki and Van Huysen, 1963;Azuma, 1970;Lopez Otero et al, 1973;Heller and Nanda, 1979;Yamasaki et al, 1980;Lilya et al, 1984;Martinez and Johnson, 1987;Chao et al, 1988;Lee, 1990;King et al, 1991a, b;King and Keeling, 1995;Ashizawa and Sahara, 1998). This compensatory bone deposition results from enhanced differentiation of osteoblasts from precursor cells within the PDL and the alveolar bone coincident to the tensile forces during the first 4 days of tooth movement (Pavlin and Gluhak-Heinrich, 2001), the time period used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In response to these forces, bone is deposited on the alveolar wall in regions of tension, and bone resorption occurs at sites experiencing pressure forces (Macapanpan et al, 1954;Waldo and Rothblatt, 1954;Zaki and Van Huysen, 1963; Azuma, 1970;Lopez Otero et al, 1973;Heller and Nanda, 1979;Yamasaki et al, 1980;Lilya et al, 1984;Martinez and Johnson, 1987; Chao et al, 1988;Lee, 1990; King et al, 1991a, b;King and Keeling, 1995; Ashizawa and Sahara, 1998). Rat molar teeth drift in a distal direction under physiologic conditions because the alveolus maintains net bone deposition on its mesial surface and net bone resorption on its distal surface (Sicher and Weinmann, 1944).…”
Section: Introductionmentioning
confidence: 99%